“Together we go far”: Exploring the motivational dispositions within connected fitness - Melissa Davies; Thomas Aicher; Brianna Newland; Eric Hungenberg (Journal of Applied Sports Management, 2024)
This study examined the motivational profiles of connected fitness users to better position brands as they compete with the reopening of physical gyms and in-person classes. Using survey responses from 663 Peloton users, a K-cluster analysis was performed to identify three clusters of Peloton users (Wellness, Physique, and Social Performance), based on their motives for using the brand’s app. Findings suggest that connected fitness brands should leverage their ability to create social engagement and challenging opportunities to better their own past performance to differentiate themselves and retain users in a very cluttered and competitive marketplace.
Keywords: connected fitness; exercise motivation; brand community; brand equity